Total Quality Management and Productivity of Steel Threading Firm in Port Harcourt - Yereba Baridakara; Mgbataogu, Ifeanyi S. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Organizational productivity refers to the ability of an organization to effectively utilize its resources to achieve its goals and objectives efficiently. It is a measure of how efficiently an organization utilizes its inputs (such as labor, capital, technology, and materials) to produce desired outputs (products or services) within a given time frame. Productivity is essential for meeting customer demands and expectations. Pipe threading firms in Port Harcourt are likely to serve clients in the oil and gas industry, where timely completion of projects is crucial. A productive organization can deliver services promptly, meet project deadlines, and ensure customer satisfaction.